Predictive factors for hospital self-discharge in tuberculosis admissions in the state of Rio de Janeiro, from 2011-2018: a retrospective cohort study - Marcela Bhering; Caroline Millon; Maria Eduarda Beltrão da Rosa Rinaldi; Hedi Marinho de Melo Guedes de Oliveira (Ministério da Saúde do Brasil, 2024)
ABSTRACT Objective To assess factors associated with hospital self-discharge of patients with tuberculosis in the state of Rio de Janeiro, Brazil, 2011-2018. Methods This was a retrospective cohort study in a referral hospital. Clinical and epidemiological characteristics were compared according to hospitalization outcome (self-discharge, formal discharge, or death). Hazard ratios (HR) with 95% confidence intervals (95%CI) for the association of self-discharge with explanatory variables were estimated using Cox regression. Results Of the 1429 hospitalizations, 10.4% ended in self-discharge. Female sex (HR = 1.47; 95%CI 1.03;2.11), age ≤ 42 years (HR = 2.01; 95%CI 1.38; 2.93), substance use (HR = 1.62; 95%CI 1.12; 2.34), hospitalization after treatment dropout (HR = 2.04; 95%CI 1.37; 3.04), and homelessness (HR = 2.5; 95%CI 1.69; 3.69) were associated with self-discharge. Conclusion Patients with social vulnerability require more careful monitoring during hospitalization.